Student’s Perception of the Function of Guidance and Counseling in Schools - Bella Fatmilia; Daharnis Daharnis (Jurnal Neo Konseling, 2022)
Guidance and Counseling is needed by students to assist in the development of personal life, social life, learning activities as well as planning and career development. Through Guidance and Counseling, it is hoped that the potential of each student can be explored and developed appropriately. However, in reality there are still students who do not take advantage of guidance and counseling services and do not understand the function of guidance and counseling. Guidance and Counseling has four functions, namely the functions of understanding, prevention, alleviation, and maintenance and development. This study aims to describe students perceptions of the function of guidance and counseling in schools. This study uses a quantitative descriptive research method. The population used in this study was 509 students of SMPN 7 Padang who were registered in the 2022/2023 academic year with a research sample of 255 students selected by the Proportional Random Sampling technique. Collecting data in this study using a questionnaire on student perceptions of the function of guidance and counseling. The data was processed using descriptive statistical analysis techniques. The results showed that the students perception of the function of guidance and counseling as a whole was in the good category. The results of the research on student perceptions of the function of guidance and counseling can be seen in detail as follows: (1) students perceptions of the function of understanding guidance and counseling are in the good enough category, (2) students perceptions of the prevention function of guidance and counseling are in the good category, (3) students perceptions about the function of alleviating guidance and counseling are in the good category, and (4) students perceptions about the function of maintenance and development of guidance and counseling are in the good category.